Strategi Pengembangan Bisnis Pada Industri Otomotif: Business Development Strategy in The Automotive Industry - Titis Wicaksono; Rizal Syarief; Siti Jahroh (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
PT. XYZ is part of the steel industry that focuses on the automotive sector which is very possible to increase business capacity. The decline in profit ratio in the last four years has triggered the development of a business model. The research aims to (1) identify the business model canvas of PT. XYZ, (2) analysis of the influence of internal and external factors for the company, and (3) create a business development strategy. The research was conducted using descriptive methods utilizing business model canvas, SWOT, and Blue Ocean Strategy analysis tools. Research analysis techniques based on primary and secondary data collected in February 2019 - June 2019 through the method of observation, interviews, questionnaires, and literature studies. Respondents were selected by purposive sampling technique, which is the technique for determining respondents who are considered experts and understand the situation of PT. XYZ both internal and external. The business development strategy is carried out through the development of the company's current business model canvas with a combination of blue ocean strategy perspectives based on the direction of the company's business development, evaluation of business model elements, environmental analysis. According to the research results obtained two business model development strategies where the first strategy is the improvement of cost structure elements by reducing the purchase of imported raw materials and creating components of local suppliers in the key partner elements to reduce the cost of purchasing materials. The second strategy is to improve the elements of key activities by develop business operating sistems and develop customer segments, which targets companies that manufacture two-wheeled vehicle components. Keywords: business model canvas, blue ocean strategy, automotive, SWOT, steel